Lessons Learned From The ASEAN Experience And The Potential To Benefit From It In The Arab World - Sayouh, Louay; Ghanem, Deema (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The research sheds light on the success achieved by ASEAN countries, which can be considered as a role model, especially for the Arab countries. The study followed a combination of historical and descriptive analytical approaches to shed light on the experience of ASEAN and the analysis of numbers and data. Based on the above, the research dealt with the most important ideas that serve the subject according to the following: ASEAN experience in agriculture. ASEAN experience in industry. ASEAN experience in the field of services (education). ASEAN Strategy for 2020. يلقي البحث الضوء على النجاح الذي حققته دول الآسيان، حيث يمكن اعتبارها نموذجاً يحتذى به خاصة بالنسبة للدول العربية، ويهدف البحث إلى الحديث عن تجربة الآسيان في مجال الزراعة والصناعة والخدمات (التعليم)، وهل يمكن الاستفادة من هذه التجربة بالنسبة للدول العربية. اتبعت الدراسة مزيج من المنهج التاريخي والمنهج الوصفي التحليلي وذلك لإلقاء الضوء على تجربة الآسيان وتحليل الأرقام والبيانات. وبناء على ما تقدم تناول البحث أهم الأفكار التي تخدم الموضوع وفقاً لما يأتي: تجربة الآسيان في مجال الزراعة. تجربة الآسيان في مجال الصناعة. تجربة الآسيان في مجال الخدمات (التعليم). استراتيجية الآسيان لعام 2020.